A generalized fractal dynamics option pricing model with transaction costs - Angkola, Francisca (Curtin University, 2016)
Since the introduction of classical Black-Scholes model, option pricing is an area which has been studied by many researchers worldwide with the prospect to develop a better, more realistic model than the existing ones. We improve the existing model to capture long memory in the financial market by considering generalized fractal dynamics and transaction costs. The influences and relevance of various additional parameters on the real financial market are also investigated in this work.